Regression approach to technical reserve calculation - Dao Thi Ha, Phuong; Zimmermann, Pavel, 1980-; Sládek, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
In this thesis, we consider several existing models in a claims reserving problem. We compare the triangle model and generalized linear models (GLM) through their predictions. Both the theory of GLM as well as reserving theory are discussed. The practical part of our work is focused on the application GLM techniques and comparison of these models on real data represented by a non-life insurance portfolio. Mean squared error of prediction (MSEP) and bootstrapping are used to compare these models. Our goal is to find the structure of the best model suited for the given dataset measured using quality assessments.
Vedoucí práce: Pavel Zimmermann
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses